Synthesis of Chiral Tertiary Amine–Thioureas Based on Spirobiindane and Application in Catalytic Asymmetric Michael Addition Reaction - Han, Zhao; Lin, Xufeng (Synthesis, 2020)
A series of novel chiral bifunctional tertiary amine–thioureas based on spirobiindane were designed and synthesized as organocatalysts. One of these catalysts was shown to promote the asymmetric Michael addition reaction of 1,3-diphenylpropane-1,3-dione to nitroolefins, affording the desired products in good yields (up to 95%) and enantioselectivities (up to 98% ee).
Keywords: organocatalysis; Michael addition; nitroolefins; spiro skeleton; thiourea